Unsupervised Link Discovery through Knowledge Base Repair - Ngonga Ngomo, Axel-Cyrille; Ahmed Sherif, Mohamed; Lyko, Klaus (The Semantic Web: Trends and Challenges - 11th International Conference, ESWC 2014, Anissaras, Crete, Greece, May 25-29, 2014. Proceedings)

LinkLion: A Link Repository for the Web of Data - Nentwig, Markus; Soru, Tommaso; Ngonga Ngomo, Axel-Cyrille; Rahm, Erhard (The Semantic Web: ESWC 2014 Satellite Events - ESWC 2014 Satellite Events, Anissaras, Crete, Greece, May 25-29, 2014, Revised Selected Papers)

Hybrid Acquisition of Temporal Scopes for RDF Data - Rula, Anisa; Palmonari, Matteo; Ngonga Ngomo, Axel-Cyrille; Gerber, Daniel; Lehmann, Jens; Bühmann, Lorenz (The Semantic Web: Trends and Challenges - 11th International Conference, ESWC 2014, Anissaras, Crete, Greece, May 25-29, 2014. Proceedings)

conTEXT - Lightweight Text Analytics Using Linked Data - Khalili, Ali; Auer, Sören; Ngonga Ngomo, Axel-Cyrille (The Semantic Web: Trends and Challenges - 11th International Conference, ESWC 2014, Anissaras, Crete, Greece, May 25-29, 2014. Proceedings)

A comparison of supervised learning classifiers for link discovery - Soru, Tommaso; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 10th International Conference on Semantic Systems, SEMANTICS 2014, Leipzig, Germany, September 4-5, 2014)

Towards an open question answering architecture - Marx, Edgard; Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille; Höffner, Konrad; Lehmann, Jens; Auer, Sören (Proceedings of the 10th International Conference on Semantic Systems, SEMANTICS 2014, Leipzig, Germany, September 4-5, 2014)

A service-oriented search framework for full text, geospatial and semantic search - Both, Andreas; Ngonga Ngomo, Axel-Cyrille; Usbeck, Ricardo; Lukovnikov, Denis; Lemke, Christiane; Speicher, Maximilian (Proceedings of the 10th International Conference on Semantic Systems, SEMANTICS 2014, Leipzig, Germany, September 4-5, 2014)

A tool suite for creating question answering benchmarks - Ngonga Ngomo, Axel-Cyrille; Heino, Norman; Speck, René; Malakasiotis, Prodromos (Proceedings of the Ninth International Conference on Language Resources and Evaluation, LREC 2014, Reykjavik, Iceland, May 26-31, 2014)

Introduction to Linked Data and Its Lifecycle on the Web - Ngonga Ngomo, Axel-Cyrille; Auer, Sören; Lehmann, Jens; Zaveri, Amrapali (Reasoning Web. Reasoning on the Web in the Big Data Era - 10th International Summer School 2014, Athens, Greece, September 8-13, 2014. Proceedings)

HELIOS - Execution Optimization for Link Discovery - Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2014 - 13th International Semantic Web Conference, Riva del Garda, Italy, October 19-23, 2014. Proceedings, Part I)

Cross-Document Coreference Resolution Using Latent Features - Ngonga Ngomo, Axel-Cyrille; Röder, Michael; Usbeck, Ricardo (Proceedings of the Second International Workshop on Linked Data for Information Extraction {(LD4IE} 2014) co-located with the 13th International Semantic Web Conference {(ISWC} 2014), Riva del Garda, Italy, October 20, 2014)

Time-efficient execution of bounded Jaro-Winkler distances - Dreßler, Kevin; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 9th International Workshop on Ontology Matching collocated with the 13th International Semantic Web Conference {(ISWC} 2014), Riva del Garda, Trentino, Italy, October 20, 2014)

Web-Scale Extension of RDF Knowledge Bases from Templated Websites - Bühmann, Lorenz; Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille; Saleem, Muhammad; Both, Andreas; Crescenzi, Valter; Merialdo, Paolo; Qiu, Disheng (The Semantic Web - ISWC 2014 - 13th International Semantic Web Conference, Riva del Garda, Italy, October 19-23, 2014. Proceedings, Part I)

Named Entity Recognition using FOX - Speck, René; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2014 Posters {&} Demonstrations Track a track within the 13th International Semantic Web Conference, ISWC 2014, Riva del Garda, Italy, October 21, 2014)

Multilingual Disambiguation of Named Entities Using Linked Data - Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille; Luo, Wencan; Wesemann, Lars (Proceedings of the ISWC 2014 Posters {&} Demonstrations Track a track within the 13th International Semantic Web Conference, ISWC 2014, Riva del Garda, Italy, October 21, 2014)

AGDISTIS - Graph-Based Disambiguation of Named Entities Using Linked Data - Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille; Röder, Michael; Gerber, Daniel; Athaide Coelho, Sandro; Auer, Sören; Both, Andreas (The Semantic Web - ISWC 2014 - 13th International Semantic Web Conference, Riva del Garda, Italy, October 19-23, 2014. Proceedings, Part I)

Ensemble Learning for Named Entity Recognition - Speck, René; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2014 - 13th International Semantic Web Conference, Riva del Garda, Italy, October 19-23, 2014. Proceedings, Part I)

SAFE: Policy Aware SPARQL Query Federation Over RDF Data Cubes - Khan, Yasar; Saleem, Muhammad; Iqbal, Aftab; Mehdi, Muntazir; Hogan, Aidan; Ngonga Ngomo, Axel-Cyrille; Decker, Stefan; Sahay, Ratnesh (Proceedings of the 7th International Workshop on Semantic Web Applications and Tools for Life Sciences, Berlin, Germany, December 9-11, 2014)

From RDF to Natural Language and Back - Gerber, Daniel; Ngonga Ngomo, Axel-Cyrille (Towards the Multilingual Semantic Web, Principles, Methods and Applications)

Proceedings of the 9th International Workshop on Ontology Matching collocated with the 13th International Semantic Web Conference (ISWC 2014), Riva del Garda, Trentino, Italy, October 20, 2014

A Technical Concept for Plant Engineering by Simulation-Based and Logistic-Integrated Project Management - Gutfeld, Thomas; Jessen, Ulrich; Wenzel, Sigrid; Laroque, Christoph; Weber, Jens (Proceedings of the 2014 Winter Simulation Conference)

A Data Mining Approach to Support a Data-Driven Scheduling System for Air Cargo Terminals - Boxnick, Simon; Lauck, Sebastian; Weber, Jens (Proceedings of the IEEE Asia-Pacific World Congress on Computer Science and Engineering 2014 (APWC on CSE 2014))

Experiments using Meta-Heuristics to Shape Experimental Design for a Simulation-Based Optimization System: Intelligent Configuration and Setup of Virtual Tooling - Weber, Jens; Boxnick, Simon; Dangelmaier, Wilhelm (Proceedings of the IEEE Asia-Pacific World Congress on Computer Science and Engineering 2014 (APWC on CSE 2014))

Applying GPU Programming to Obtain Average AS/RS Performance in Optimal Zoned Aisles - Lauck, Sebastian; Boxnick, Simon; Kopecki, Lukas (Proceedings of the IEEE Asia-Pacific World Congress on Computer Science and Engineering 2014 (APWC on CSE 2014))

Analyzing Supply Chain nodes in Heterogeneous Environments based on Transaction Data with Respect to Independent item Behavior - Lauck, Sebastian; Boxnick, Simon; Kopecki, Lukas (Proceedings of the 2nd International Conference on Advances in Computing, Electronics and Communication (ACEC-2014))

System Thinking: Crafting Scenarios for Prescriptive Analytics - Weber, Jens; Minhee, Cho; Lee, Mikyoung; Song, Sa-kwang; Geierhos, Michaela; Jung, Hanmin (Proceedings of the First International Workshop on Patent Mining and Its Applications (IPAMIN) 2014)

SentiBA: Lexicon-based Sentiment Analysis on German Product Reviews - Dollmann, Markus; Geierhos, Michaela (Konvens 2014 Workshop Proceedings)

Linked Open Data System for Scientific Data Sets - Baeumer, Frederik Simon; Gim, Jangwon; Jeong, Do-Heon; Geierhos, Michaela; Jung, Hanmin (Proceedings of the First International Workshop on Patent Mining and Its Applications (IPAMIN) 2014)

„Ich bin dafür, dass...“ Kinder gewinnen Standpunkte - Büker, Petra (Praxis Deutsch, Sonderheft: Durch die Schuljahre 5/6)

The Development of Intercultural Pedagogy and its Influences on the German Primary School: Conclusions and Perspectives - Hüpping, Birgit; Büker, Petra (Intercultural Education)

Entwicklung einer gemeinsamen Bildungsdokumentation für KiTa und Grundschule: Chancen, Hürden und Gelingensbedingungen aus der Perspektive von Erzieherinnen und Grundschullehrer/innen - Büker, Petra (Individuelle Förderung und Lernen in der Gemeinschaft. Tagungsband zur 21. Jahrestagung der Kommission "Grundschulforschung und Pädagogik der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft. (Jahrbuch Grundschulforschung; Bd.17))

Forschendes Lernen und Studieren in der neuen Grundschullehrerausbildung. Konzepte und Projekte aus NRW - Röhner, Charlotte; Büker, Petra; Bunte, Nicola; Miller, Susanne; Velten, Katrin; Wiesemann, Jutta (Individuelle Förderung und Lernen in der Gemeinschaft. Tagungsband zur 21. Jahrestagung der Kommission "Grundschulforschung und Pädagogik der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft. (Jahrbuch Grundschulforschung; Bd. 17))

Gelingensbedingungen für die Gestaltung von Kooperation. Ausgewählte Ergebnisse aus drei Jahren wissenschaftlicher Begleitung des Modellprojekts "Kinderbildungshaus Paderborn". Vortrag im Rahmen der Veranstaltung zur Auszeichnung der Bildungshaus-Partner durch das Bildungsbüro der Stadt Paderborn - Büker, Petra; Bührmann, Thorsten; Kordulla, Agnes
Oktober 2014

Kind- und Ressourcenorientierung als Kernprinzipien der Grundschulpädagogik und der Inklusion. Beitrag im Rahmen des Symposiums: Grundschulpädagogik und Inklusion. Die neuen Förderpädagogischen Studiengänge in NRW an der 23. Jahrestagung der Kommission Grundschulforschung und Pädagogik der Primarstufe an der Universität Leipzig - Büker, Petra
September 2014

Peer Learning in altersgemischten Lerngruppen im Übergang Kita - Grundschule aus der Perspektive von Kindern. Posterbeitrag an der 23. Jahrestagung der Kommission Grundschulforschung und Pädagogik der Primarstufe an der Universität Leipzig - Büker, Petra; Kordulla, Agnes
September 2014

Quality of peer-interaction in mixed-age learning settings – in the transition process from kin-dergarten to primary school. Poster presentation at the 24th EECERA conference - European Early Childhood Education Research Association. Crete, Greece - Büker, Petra; Kordulla, Agnes
September 2014

Bildung für die Zukunft unserer Kinder. Vortrag im Rahmen des 7. BOW-Gesprächs 2014 (Bildungswerk der ostwestfälisch-lippischen Wirtschaft) im b.i.b. International College in Paderborn - Büker, Petra
September 2014

The common stomach: Organizing task allocation in wasp societies - Hamann, Heiko; Karsai, Istvan; Schmickl, Thomas; Hilbun, Allison (Symposium on Biomathematics and Ecology: Education and Research)

Swarm in a Fly Bottle: Feedback-Based Analysis of Self-organizing Temporary Lock-ins - Hamann, Heiko; Valentini, Gabriele (Ninth Int. Conf. on Swarm Intelligence (ANTS 2014))

Optimal Control with Uncertainty - Seifried, A.; Ober-Blöbaum, S. (Dependability of Self-Optimizing Mechatronic Systems)

Introduction to Self-optimization and Dependability - Trächtler, Ansgar; Hölscher, Christian; Rasche, Christoph; Priesterjahn, Claudia; Zimmer, Detmar; Henning Keßler, Jan; Stahl, Katharina; Flaßkamp, Kathrin; Vaßholz, Mareen; Krüger, Martin; Dellnitz, Michael; Iwanek, Peter; et al. (Dependability of Self-Optimizing Mechatronic Systems)

Methods of Improving the Dependability of Self-optimizing Systems - Seifried, Albert; Trächtler, Ansgar; Kleinjohann, Bernd; Heinzemann, Christian; Rasche, Christoph; Priesterjahn, Claudia; Steenken, Dominik; Ramming, Franz-Josef}; Wehrheim, Heike; Henning Keßler, Jan; Gausemeier, Jürgen; Stahl, Katharin; et al. (Dependability of Self-Optimizing Mechatronic Systems)

Analysis of Swarm Behaviors Based on an Inversion of the Fluctuation Theorem - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl (Artificial Life)
A grand challenge in the field of artificial life is to find a general theory of emergent self-organizing systems. In swarm systems most of the observed complexity is based on motion of simple entities. Similarly, statistical mechanics focuses on collective properties induced by the motion of many interacting particles. In this article we apply methods from statistical mechanics to swarm systems. We try to explain the emergent behavior of a simulated swarm by applying methods based on the fluctuation theorem. Empirical results indicate that swarms are able to produce negative entropy within an isolated subsystem due to frozen accidents. Individuals of a swarm are able to locally detect fluctuations of the global entropy measure and store them, if they are negative entropy productions. By accumulating these stored fluctuations over time the swarm as a whole is producing negative entropy and the system ends up in an ordered state. We claim that this indicates the existence of an inverted fluctuation theorem for emergent self-organizing dissipative systems. This approach bears the potential of general applicability.

Self-Organized Collective Decision Making: The Weighted Voter Model - Dorigo, Marco; Hamann, Heiko; Valentini, Gabriele; Lomuscio, Alessio; Scerri, Paul; Bazzan, Ana; Huhns, Michael (Proceedings of the 13th Int. Conf. on Autonomous Agents and Multiagent Systems (AAMAS 2014))
Collective decision making in self-organized systems is challenging because it relies on local perception and local communication. Globally defined qualities such as consensus time and decision accuracy are both difficult to predict and difficult to guarantee. We present the weighted voter model which implements a self-organized collective decision making process. We provide an ODE model, a master equation model (numerically solved by the Gillespie algorithm), and agent-based simulations of the proposed decision-making strategy. This set of models enables us to investigate the system behavior in the thermodynamic limit and to investigate finite-size effects due to random fluctuations. Based on our results, we give minimum requirements to guarantee consensus on the optimal decision, a minimum swarm size to guarantee a certain accuracy, and we show that the proposed approach scales with system size and is robust to noise.

Evolving Prediction Machines: Collective Behaviors Based on Minimal Surprisal - Hamann, Heiko (Int. Conf. on Genetic and Evolutionary Computation (GECCO 2014))

Sorting in Swarm Robots Using Communication-Based Cluster Size Estimation - Birattari, Mauro; Dorigo, Marco; Hamann, Heiko; Garnier, Simon; Montes de Oca, Marco; Solnon, Christine; Stuetzle, Thomas; Ding, Hongli (Ninth Int. Conf. on Swarm Intelligence (ANTS 2014))

Derivation of a Micro-Macro Link for Collective Decision-Making Systems: Uncover Network Features Based on Drift Measurements - Khaluf, Yara; Dorigo, Marco; Hamann, Heiko; Valentini, Gabriele; Bartz-Beielstein, T. (13th International Conference on Parallel Problem Solving from Nature (PPSN 2014))

Evolution of Collective Behaviors by Minimizing Surprise - Hamann, Heiko; Sayama, Hiroki; Rieffel, John; Risi, Sebastian; Doursat, Rene; Lipson, Hod (14th Int. Conf. on the Synthesis and Simulation of Living Systems (ALIFE 2014))

A Swarm Robotics Approach to Task Allocation Under Soft Deadlines and Negligible Switching Costs - Cervera, Enric; Khaluf, Yara; Birattari, Mauro; Hamann, Heiko; Pobil, Angel P. del; Chinellato, Eris; Martinez-Martin, Ester; Hallam, John; Morales, Antonio (Simulation of Adaptive Behavior (SAB 2014))

A Review Corpus for Argumentation Analysis - Wachsmuth, Henning; Trenkmann, Martin; Stein, Benno; Engels, Gregor; Palakarska, Tsvetomira (Proceedings of the 15th International Conference on Intelligent Text Processing and Computational Linguistics)